PERBEDAAN STATUS STUNTING BERDASARKAN POLA MAKAN DAN PENERAPAN PHBS PADA KELUARGA BALITA DI WILAYAH UPTD PUSKESMAS MENGWI I - Hertog Nursanyoto; I Komang Agusjaya Mataram; Ni Gusti Ayu Putu Sinta Utami Intania (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2023)
Stunting is a health problem that causes sufferers to get sick easily and have a body posture that is not optimal as an adult. The condition of failure to thrive in children under five (babies under five years) results from chronic malnutrition so that children are too short for their age. The purpose of this study was to analyze differences in stunting status based on diet and the implementation of PHBS in families of toddlers in the UPTD Region of Mengwi I Health Center. This type of research was an observational study with a cross-sectional design. This research was conducted in December 2022. The determination of the sampling size was determined by using a purposive sampling technique. Based on the calculation results, a sample size of 43 samples was obtained from 3,025 toddlers at the Mengwi I Health Center. Data is presented with frequency tables and cross tables and then analyzed using the Chi Square test. The results showed that of the 43 samples, there were 28 samples (65.1%) with less eating, 25 samples (58.1%) with less eating frequency, 24 samples (55.8%) with less energy intake, 22 samples (51.2%) with good PHBS implementation, and 17 samples (39.5%) with stunting status. Statistical test results showed differences in stunting status in the UPTD Puskesmas Mengwi I area. Based on diet (type of food), frequency of eating, total intake of macronutrients and implementation of PHBS with an overall p value (p0.05)